A10.27 Systemic Sclerosis – Role of Agonistic Autoantibodies Directed Against the Angiotensin Receptor Type 1 and the Endothelin Receptor Type A on Immune Cells in Disease Pathogenesis. (25th February 2013) - Günther, J; Kill, A; Becker, MO; Riemekasten, G
Abstract : Background and Objectives: Agonistic autoantibodies against the angiotensin receptor type 1 (AT1R) and the endothelin receptor type A (ETAR) have been identified in the majority of systemic sclerosis (SSc) patients. We proved the expression of the AT1R and the ETAR on human peripheral immune cells. Here, we investigated the effects of these autoantibodies on human immune cells in vitro, the association with clinical data, and their possible role in the pathogenesis of systemic sclerosis. Methods: Peripheral blood mononuclear cells (PBMCs) from healthy donors were isolated by gradient centrifugation and in vitro stimulated by affinity-purified IgG from SSc patients containing anti-AT1R and anti-ETAR antibodies as well as by affinity-purified IgG from healthy donors. After stimulation the protein expression of cytokines was measured by ELISA. T cells were isolated from PBMCs by magnetically activated cell sort (MACS) and cultivated in antiCD3/CD28 coated plates. Afterwards, migration assays were performed towards IgGs of SSc patients or healthy donors. Results: IgG of SSc patients induced a significantly increased expression and secretion of IL-8 and an abundant but due to a broad range not significant secretion of CCL18. T cell migration towards IgG of SSc patients was increased. All these effects were significantly reduced by commercial AT1R and ETAR antagonist, confirming the specifity of the biological activity of the autoantibodies. Correlation analysis with clinical data of the SSc IgG donors revealed a negative correlation of IL-8 expression with the time since disease onset, and an association of CCL18 expression with the incidence of vascular complications. The chemotactic motility of T cells correlated with the autoantibody titers of the used SSc IgG. Conclusions: SSc patient IgGs containing anti-AT1R and anti-ETAR antibodies seem to have effects on inflammation and fibrosis. IL-8 is a major inflammatory cytokine, inducing migration and inflammatory effects. CCL18 is a fibrotic cytokine, also contributing to leucocyte infiltration, and to lung fibrosis in SSc and other diseases. Thus, anti-AT1R and anti-ETAR antibodies may play an important role particularly in the early stage of SSc, contributing to leucocyte infiltration, vascular inflammation and injury, which are regarded to be the first events leading to tissue damage and fibrosis.